High-performance large-area quasi-2D perovskite light-emitting diodes - Changjiu Sun (Nature Portfolio, 2021)
Performance of perovskite LED tends to decline as the active area increases, thus understanding the failure mechanism is paramount to surmount this limitation. Here, the authors report severe phase-segregation to be the cause, and introduce L-Norvaline to overcome it, as the result, highly-efficient 9.0 cm2 green PeLED is realised.